Analysis of the Effect of E-Satisfaction and E-Trust on Loyalty in E-Commerce - Putra, Jerry Aldian; Hidayat, Anas (Archives of Business Research, 2022)
This research aims to analyze the effect of e-satisfaction and e-trust on attitudinal loyalty and behavioral loyalty in e-commerce in Indonesia. This research also analyzed the effect of behavioral loyalty on attitudinal loyalty. This research used SEM (Structural Equation Model) AMOS version 24 and the data collection used questionnaire method. The population in this research were undergraduate students who had at least 2 times shopping at e-commerce. There were 254 respondents in this research. The results obtained that e-trust had positive and significant effect on e-satisfaction, and e-satisfaction had positive and significant effect on attitudinal loyalty and behavioral loyalty. However, in the research, it was found that e-trust had negative and significant effect on attitudinal loyalty, and e-trust had positive but insignificant effect on behavioral loyalty. In this research, it was also found that behavioral loyalty had positive and significant effect on attitudinal loyalty.